Glyphosate affects swine ovarian and adipose stromal cell functions - Gigante, Paolo; Berni, Melissa; Bussolati, Simona; Grasselli, Francesca; Grolli, Stefano; Ramoni, Roberto; Basini, Giuseppina (Animal reproduction science, 2018)
•Glyphosate (GLY) is the most used pesticide.•We investigated GLY effects in swine granulosa and adipose stromal cells.•GLY affects granulosa cell growth, steroidogenesis and redox status.•GLY affects adipose stromal cells proliferation and differentiation.•GLY exposure can represent an health risk. Although Glyphosate (GLY) is a widely used pesticide, its effects on ovarian function and stem cell differentiation are still largely unknown. Therefore, as a contribution on this subject, the present work reports an investigation of the in vitro effects of GLY on swine granulosa cells and adipose stromal cells (ASCs). The effect of GLY at different doses (0.2, 4 and 16 μg/mL) was evaluated on granulosa cells growth (BrDU incorporation and ATP production), steroidogenesis (17-β estradiol and progesterone secretion) and redox status (superoxide and nitric oxide production and non-enzymatic scavenging activity). GLY has been shown to inhibit cell growth, 17-β estradiol and non-enzymatic scavenging activity and to increase progesterone and nitric oxide secretion (P < 0.05). In addition, GLY significantly decreased the viability of ASCs (P < 0.001), and inhibited their adipogenic differentiation. These data indicate that GLY alters the main features of granulosa cells and ASCS thus suggesting that GLY could affect both reproductive function and adipose tissues homeostasis.